Environment and The Students’ Motivation in Studying Indonesian as a Foreign Language at GoBali Program, The University of Udayana-Bali - Sari Dewi, Anak Agung Sagung Shanti (Lingual Journal of Language and Culture, 2020)
This study  focuses on analysing the students’motivation for studying Indonesian as a foreign language at Go Bali, a one-semester international study program  at the University of Udayana,  particularly investigating the students’motivation during the course and analyse how the environment influences their learning motivation. This study involved 76 foreign students and 4 instructors in four Indonesian Language classrooms at the program and the data were collected through survey techniques, classroom observations and interviews. The results show that the students’ motivation in learning Bahasa Indonesia is varied and in general is relatively low. However, the environment where they study the language has actually given an advantages for most students in which they become more motivated to pick up the knowledge of the language for their daily lives in Bali, apart from whether it will give further benefits for their future or not.